Pengaruh Pembelajaran Ngudi Susilo terhadap Akhlak Santri Diniyah Ula di TPQ Assalam - Zuhriyyah Hidayati; Abu Amar; Azizatul Maghfiroh (Rihlah Review: Jurnal Pendidikan Islam, 2022)
The purpose of this study was to determine the effect of ngudi susilo learning on the morals of the diniyah ula students at TPQ Assalam Ngayung Lamongan. This study uses a quantitative research approach. The sample taken is a population of 21 students. To collect the data obtained in this study, the researchers used research instruments, including questionnaires and observations. Data analysis techniques in this study are editing and scoring. Ngudi Susilo learning at TPQ Assalam Ngayung is included in the good category with a percentage yield of 63.30%. The morals of Diniyah Ula students at TPQ Assalam Ngayung are included in the Enough category with a percentage of 59.47%. There is an influence between ngudi susilo learning and the morals of Diniyah Ula students at TPQ Assalam Ngayung in the 2021/2022 academic year with an rxy (r count) of 0.548 and between Variable X (Ngudi Susilo's Learning) and Variable Y (Akhlak of Diniyah Ula students) there is a significant correlation Medium with the value is assessed between 0.41-0.60